2013
DOI: 10.1109/lgrs.2012.2207704
|View full text |Cite
|
Sign up to set email alerts
|

GPS Near-Real-Time Coseismic Displacements for the Great Tohoku-oki Earthquake

Abstract: Here, we present the application to the great Tohoku-oki (Japan) earthquake (United States Geological Survey M = 9.0, March 11, 2011, 05: 46: 24 Coordinated Universal Time) of a novel approach, named Variometric Approach for Displacements Analysis Stand-Alone Engine, able to estimate accurate coseismic displacements and waveforms in real time, in the global reference frame, just using the standard broadcast products (orbits and clocks) and the high-rate (1 Hz or more) carrier phase observations continuously co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…The mean RMSEs of them are 2.4, 2.5, and 3.7 cm in the east, north, and up components, respectively. The RMSEs reveal that the integrated displacements can achieve centimeter‐level accuracy, which are consistent with previous publications such as Colosimo et al () and Branzanti et al ().…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The mean RMSEs of them are 2.4, 2.5, and 3.7 cm in the east, north, and up components, respectively. The RMSEs reveal that the integrated displacements can achieve centimeter‐level accuracy, which are consistent with previous publications such as Colosimo et al () and Branzanti et al ().…”
Section: Resultssupporting
confidence: 91%
“…Displacements can be obtained from a single integration of velocities, which is subject to an induced trend in the displacements due to residual errors in the velocity estimates such as satellite orbit and clock errors, atmospheric errors, and multipath effects. By applying a method of detrending, displacements with centimeter‐level accuracy can be obtained (Benedetti et al, ; Branzanti et al, ; Colosimo et al, ; Geng et al, ; Hung et al, ). The variometric approach has advantages over relative positioning and PPP.…”
Section: Introductionmentioning
confidence: 99%
“…High-rate GNSS has been a hot research topic recently and found a lot of applications in earth sciences and civil engineering (see e.g., Kato et al 2000;Larson et al 2003;Larson 2009;Smalley 2009;Grapenthin and Freymueller 2011;Branzanti et al 2013;Moschas and Stiros 2015;Xu et al 2013Xu et al , 2019. A number of methods have been proposed to ensure high precision high-rate GNSS waveform and displacement measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal solution would be when the data coming from the sensors could be processed immediately and continuously. Classic procession of high volume data result in very bad performance; they require new approach [9] and also traditional SQL queries does not scale well, i.e. : with an increasing data set the SQL queries take more and more time [8] to be processed.…”
Section: Related Workmentioning
confidence: 99%